miRNAs Delivery for Cancer-associated Fibroblasts' Activation and Drug Resistance in Cancer Microenvironment - Anajafi, Sara; Paryan, Mahdi; Khoshnazar, Amineh; Soleimani, Masoud; Mohammadi-Yeganeh, Samira (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Cancer-associated fibroblasts (CAFs) as a major component of cancer stroma contribute to diverse procedures of most solid tumors and might be a targeted cancer therapy approach. Their specified features, related signaling pathways, distinct biomarkers, and sub-populations need to be deciphered. There is a need for CAF extraction or induction for in vitro investigations. Some miRNAs could activate CAF-like phenotype and they also interfere in CAF-mediated drug resistance, aggressiveness, and metastatic behaviors of several cancer cell types. Due to the complex relevance of miRNA and CAFs, these non-coding oligonucleotides may serve as attractive scope for anti-cancer targeted therapies, but the lack of an efficient delivery system is still a major hurdle. Here, we have summarized the investigated information on CAF features, isolation, and induction procedures, and highlighted the miRNA-CAF communications, providing special insight into nano-delivery systems.
Keywords: drug resistance